Consumer debt management among government employees: cognitive, emotional and behavioural / Nurazleena Ismail and Hilmiah Ahmad - Ismail, Nurazleena; Ahmad, Hilmiah (2023)
Many people claim that they feel burdened with their debt such as personal loans, hire purchases, housing loans, credit cards, and education loans. The burden that they carry has affected their life such as being unable to pay their debts. They want to live in luxury without thinking about the effect that will drag them to bankruptcy because of many factors that occur while managing their consumer debt. Thus, this study aims to examine the relationship between cognitive, emotional, and behavioural, and consumer debt management among government employees. This study is a descriptive study that distributed a questionnaire to collect the data and used SPSS to analyse the data. The target population is individuals who are employees from government organizations who have experienced using credit for their daily spending, purchasing assets, financing, and investing activities. The questionnaires were equally distributed to 100 employees from 10 government organizations from different positions. It found that there is a significant relationship between behavioural and consumer debt management. However, there is no significant relationship between cognitive and emotional consumer debt management. Good debt management improves the behaviour of government employees to pay their debts every month and understand the relationship between solvency and credit history. In contrast, government employees do not seriously think of their debt and are not emotional when making a decision to do financing. Future research is necessary to investigate how culture and socioeconomic status affect cognitive processes in relation to managing debt. Research should also examine how FinTech applications, including budgeting apps and AI-powered financial guidance, impact individuals' cognitive decision-making processes and their debt management results.